Analisis Pertimbangan Hakim Pengadilan Agama terhadap Penetapan Asal Usul Anak dari Perkawinan Siri: Studi Kasus Putusan No. 340/Pdt.P/2025/PA.Wsb - Aulia Fitriani, Rahmi; Hari Widiyanto; Septian Fiktor Riyantoro (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Unregistered (siri) marriages conducted without state registration lack formal legal force and create legal uncertainty regarding a child’s status, particularly in relation to identity, lineage, and civil relations with the father. This condition may undermine the fulfillment of the child’s civil rights and population administration requirements. This study examines the role of the Religious Court and the legal considerations of judges in determining a child’s origin from a siri marriage through a case study of the Decision of the Wonosobo Religious Court Number 340/Pdt.P/2025/PA.Wsb. The research employs a normative legal method with a case study approach. The findings indicate that the Religious Court plays a significant role in providing legal certainty and protecting children’s rights by basing its decision on the principle of the best interests of the child. The determination enables the inclusion of the father’s identity on the child’s birth certificate, supports orderly population administration, and prevents discrimination against the child, without conferring legal validity on the siri marriage under state law.